The contribution of temperament and parental behaviour to the developmental outcomes of preschool children - Božiković, Tina (Array, 2020)
The aim of this study was to examine whether the dimensions of parental behavioural style contribute to the explanation of the developmental characteristics of preschool children beyond children’s temperamental characteristics. A total of 194 parents of one preschool child, of which 95.36% were mother, participated in the study. The EASI temperament survey, the Multidimensional Assessment of Parenting Scale and the Preschool Child Development Assessment Questionnaire were used. The results suggested a significant correlation between the dimensions of temperament according to the EASI model (emotionality, activity, sociability and impulsivity), the functional developmental characteristics of the child and some dimensions of parenting. No significant differences were found in the assessments of temperamental characteristics and developmental outcomes between boys and girls. The results of regression analyses showed that temperamental dimensions assessments explained significant portion of preschool children developmental outcomes variance (between 56% and 74%). Furthermore, with temperamental characteristics being controlled for, the dimensions of parental behaviour did not significantly increase portion of explained criteria variance. In addition to the limitations of the study, the results were discussed in the context of existing knowledge on the developmental outcomes of preschool children with special emphasis on the importance of recognizing and understanding temperament as an important determinant of development in early ages.